Studies on Antioxidant and Antiviral Potential of Ethanolic extract of Laurus Nobilis Against Adenovirus Type VIII: in-vitro, in-vivo and in-silico Approach - K.KESIYA; AGILANDESWARI VINOTH (International Journal of Pharma and Bio Sciences, 2018)
The purpose of this study is to evaluate invitro antiviral study, antioxidant, phytochemical screening of Laurus nobilis extract and the best molecules of the L.nobilis are identified against adenovirus receptors by molecular docking study. The plant leaf of Laurus nobilis is used in food industry, drug industry and cosmetics. Bay leaves have anti-inflammatory, antimicrobial, neuroprotective and analgesic properties. These leaves are recently used in soap making, treatment of diabetes and to prevent migraine. Adenovirus has 52 serotypes, each serotype causes various diseases to humans like respiratory disease, gastrointestinal tract disorder, conjunctivitis. 52 serotypes are divided into subgroups and they mostly affect children. The plant leaves were collected from ooty and ethanol extract was collected by maceration method. The plant compounds were identified byphytochemical screening. Cytotoxicity assay was performed to find percentage of cell viability at various concentration. The antiviral properties of bay leaf were determined by antiviral inhibition assay. Laurus nobilis extract was also used in antioxidant activity test. Major compounds of bay leaf plant were used in docking study. Through this docking study best ligand were identified against adenovirus. The plant has 4.6% of total antioxidant and 1.320nm reducing power activity by antioxidant methods. L.nobilis extract showed an antiviral activity at 100µl/ml of plant extract had 60.5% of the cell protection. In docking studies, eugenol is the best ligand against coxsackie receptor and integrin receptor. This plant extract shows its potential to inhibit the adenovirus so future research is needed to find more active compounds of this plant and its helpful for make new antiviral drug against adenovirus.